Affinity of Staphylococcus aureus for prostheses colonization compared to other bacteria. An in vitro study (Research, Society and Development, 2021)
Staphylococcus aureus biofilms have been recognized as a leading cause of multiple infections, including implant-associated infections and chronic wounds. We evaluated the colonization capacity of two distinct textured prostheses by different bacterial strains. Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Proteus mirabilis and Enterococcus faecalis were evaluated. Initially, the hydrophobicity and biofilm formation capacity were determined. Subsequently, 20 fragments of vascular prosthesis and 20 silicone prostheses were embedded in suspensions with the microorganisms and incubated. The prostheses were then sown in culture medium and incubated for 48 hours. Petri dishes were photographed and analyzed by fractal dimension. The Kruskal-Wallis test and the Dunn test were applied for the analysis of biofilm formation. To compare the mean intensity for the type of bacteria and the type of prosthesis, a general linear model was applied. Staphylococcus aureus was the bacterium with the highest colonization density in both prostheses (p = 0.0001). E. coli showed strong adherence in the biofilm formation capacity test (p = 0.0001), however, it did not colonize either prosthesis. We demonstrated that Staphylococcus aureus has a greater affinity for vascular and silicone prostheses than other bacteria.